How Sequential Organizational and Psychological Mechanisms of Servant Leadership Foster Employee Creativity? - Stella Poh; Antoni Suparno; Leny Pratiwi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
In a rapidly evolving work environment, employee creativity has become increasingly important for sustaining organizational innovation, particularly among Generation Z employees. While prior research has linked servant leadership to creative performance, the psychological processes underlying this relationship remain unclear. This study investigates whether perceived organizational support and psychological empowerment sequentially explain the influence of servant leadership on employee creativity. Using data from 224 Generation Z working students in Batam, Indonesia, the proposed model was tested through Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis revealed that servant leadership strengthens perceived organizational support, psychological empowerment, and employee creativity. Furthermore, perceived organizational support and psychological empowerment operate as sequential mediators connecting servant leadership with employee creativity. These findings underscore the value of supportive and empowering workplace conditions in encouraging creativity among Generation Z employees.